Development of an evaluation system of personal e-business competency and maturity levels. (9th November 2004) - Yoon, Chui Young; Leem, Choon Seong
An evaluation system of personal e-business competency, (ESPEC), was developed to evaluate individual e-business competency and maturity levels in enterprises of the e-business environment. ESPEC measures the requirements of e-business knowledge, skills, and mindset with evaluation indices of personal e-business maturity. The indices are customised to not only four types of business departments – strategy planning, development/ maintenance, business applications, and consulting/education – but also to three levels of business position: top manager, middle manager, and worker. Also, a maturity model of personal e-business competency is defined for interpretation of the evaluation results. The construct of the evaluation model was verified for validity and reliability by a factor analysis and reliability analysis through a pilot test. The system was applied to an assessment of actual human resources, 124 workers in an enterprise, to testify to its practical value. The case evaluation procedures include a series of questionnaires, written tests and application tests.